Nitrous Oxide in Oxygen and Air in Oxygen for Perioperative Analgesia : A Comparative study - Jawad Zahir, Muhammad Shafiq, Muhammad Salman Maqbool, Muhammad Nadeem Khan (Journal of Rawalpindi Medical College, 2008)
Background: To determine that additional dose of nalbuphine is required while using medical air instead of nitrous oxide in oxygen to maintain anaesthesia so that inadequate intra-operative analgesia could be avoided. Methods: This quasi experimental study was carried out in the Department of Anaesthesia, Holy Family Hospital, Rawalpindi, from October 2007 to March 2008. One hundred patients were selected by non probability convenient sampling. Patients between 20 to 40 years of age were included, belonging to ASA Class-I and II. They were divided into two groups (A and B) scheduled for different elective surgical procedures under general anaesthesia. Group A comprised of fifty patients who received medical air in oxygen. Group B comprised of fifty patients who received nitrous oxide in oxygen. The conduct of anaesthesia was kept same in both the groups. Patients heart rate, mean arterial pressure, pulse oximetry, ECG were monitored and requirement of additional dose of nalbuphine in both the groups was noted. Intra-operative tachycardia and hypertension indicated additional dose of nalbuphine. Average value of heart rate and blood pressure of each case was determined and the data compared and analyzed by SPSS-10. Results: Forty patients in group A did not require intra-operative additional nalbuphine while the remaining ten patients required it. Forty eight patients in group B did not require additional intra-operative nalbuphine and only two patients required it. Conclusion: The use of nitrous oxide significantly reduces the intra-operative narcotic analgesia requirement.